2002
DOI: 10.2746/042516402776250388
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of strain and stress in the equine hoof capsule using finite element methods: comparison with principal strains recorded in vivo

Abstract: Summary Finite‐element (FE) methods have great potential in equine biomechanics in evaluating mechanical stresses and strains in tissues deep within the hoof. In this study, we critically assessed that potential by comparing results of FE analyses of capsular strain with in vivo data. Nine FE models were developed, corresponding to the shape of hooves for which in vivo principal strain data are available. Each model had the wall, laminarjunction, sole and distal phalanx (PIII). In a first loading condition (LC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 17 publications
0
35
0
1
Order By: Relevance
“…The distribution of the loads and the greater MTD on the medial wall (more upright) are consistent with this notion that tubules are supportive structures. However, during hoof loading superficial wall measurements of the forces do not consistently align with tubular orientation [21]. Alternatively, greater tensile and strain forces may be occurring internally, producing a stratification of physical forces within the stratum medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of the loads and the greater MTD on the medial wall (more upright) are consistent with this notion that tubules are supportive structures. However, during hoof loading superficial wall measurements of the forces do not consistently align with tubular orientation [21]. Alternatively, greater tensile and strain forces may be occurring internally, producing a stratification of physical forces within the stratum medium.…”
Section: Discussionmentioning
confidence: 99%
“…Previous works have observed that the primary epidermal laminae (PEL) densities vary in different horse populations and this variation may relate to stresses along the hoof wall [2,6,10,21]. However, studies examining equine hoof wall tubules and/or tubular density have not yet shown, if or how tubular architecture may vary or respond to environmental forces in ways similar to laminae.…”
mentioning
confidence: 99%
“…These test simulation results show that the material model is capable of reproducing the measured tissue behaviour. Following Thomason et al . (2002) we used the same material properties for the solar dermis as the laminar junction.…”
Section: Methodsmentioning
confidence: 99%
“…Other authors (Hinterhofer et al . 2000; Thomason et al . 2002) used a value for the Young's modulus of the sole tissue that corresponded to about one‐third of the mean wall stiffness.…”
Section: Methodsmentioning
confidence: 99%
“…This aspect of the model has been derived directly from published experimental data (Hinterhofer et al 1998 [5]; Douglas et al 1998 [6]; Kasapi and Gosline 1999 [7]). The load response of hoof tissues, and in particular the laminar junction and hoof wall tissues, is one aspect of this model in which we have a good degree of confidence.…”
Section: Insight From Modelling Can Address Controversial Observationsmentioning
confidence: 99%